KAJIAN TENTANG TINGKAT PERSENTASE KEBUNTINGAN PADA SAPI HASIL SINKRONISASI BERAHI DAN OPTIMALISASI INSEMINASI BUATAN PROGRAM UPSUS SIWAB TAHUN 2018 DI KABUPATEN KEEROM - Kondong, Dortje Janet; Tharukliling, Selvia (Jurnal Pertanian Terpadu Santo Thomas Aquinas, 2022)
The aim of this research were: (1) to know the percentage level of pregnancy resulting fromestrus synchronization and optimization of Artificial Insemination in the Upsus Siwab program inKeerom Regency, (2) to know the optimization level of Artificial Insemination in the 2018 UpsusSiwab program in Keerom Regency. The research method used survey methods, interviews anddocumentation. The research variable consisted of 2 variables related to estrus synchronizationactivities and optimization of artificial insemination in the 2018 Upsus Siwab program in KeeromRegency which included: (1) The percentage level of pregnancy resulting from estrussynchronization (2) The optimization level of Artificial Insemination. The results were: (1)Increasing the number of estrus synchronization acceptors; (2) The percentage of pregnancywas 61.5%; (3) The results of optimization of artificial insemination included: (a) Inseminationservice rate per pregnancy 1.62; (b) Birth rate 63 – 64%; (c) Treatment of reproductive disorders115 acceptors.